PRINSIP DUE PROCESS OF LAW DALAM PEMBARUAN HUKUM ACARA PIDANA TERHADAP EKSISTENSI PRAPERADILAN - Alam Suryo Laksono (Ensiklopedia of Journal, 2026)
Pretrial is a means of evaluating the investigation, inquiry, and prosecution process. The dynamics of criminal procedural law reform touch on the pretrial aspect to ensure due process of law. The principle of due process of law is a fundamental pillar in a state based on the rule of law that guarantees the protection of human rights, particularly in the criminal justice process. This article aims to analyze the principle of due process of law in the reform of criminal procedural law regarding the existence of pretrial. This research uses a normative juridical method with a statutory, conceptual, and comparative approach. The results of the discussion indicate that the principle of due process of law in the reform of criminal procedural law regarding the existence of pretrial still requires improvement, not only in the regulatory aspect regarding the object and subject of pretrial, especially in the aspect of pretrial organizers as the executor of authority. Integrity, professionalism, and uniformity of interpretation of pretrial are mandatory, so that the norms that aspire to realize due process of law do not lose their meaning in their orientation. Pretrial does not only function as a procedural instrument, but also as a substantive means to guarantee the protection of human rights, legal certainty, and justice in accordance with the principle of due process of law. Furthermore, the legal implications of the reform of criminal procedural law regarding the existence of pretrial proceedings open up space for both the object and subject of pretrial proceedings. However, there is potential for functional degradation if it does not address the administrative aspects, including the single judge and the duration of the trial. Pretrial proceedings are still implemented formally and are limited to purely procedural aspects without substantial testing.Keywords: Due Process of Law, Criminal Procedure Law, Pretrial